Is a move up the job ladder an escape from poverty? - Samuel Ampaw; Michael Danquah; Rajesh S. N. Raj; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Using panels of labour force surveys from Ghana, South Africa, Tanzania, Uganda, and India and a recent work status classification, we provide an in-depth analysis of labour mobility up or down the job ladder. This classification allows us to observe job transition possibilities across six work status groups. We examine factors driving upward mobility and probe its association with poverty. We find that people seldom transition from one work status to another across all countries. The prevalence of downward mobility is similar to upward mobility in the four African countries and India. Many remain in the same sector even after moving up the job ladder. Among those who move up the ladder, a considerable majority move into the service sector. Transition into industry remains very low. Additionally, environmental factors such as access to electricity, improved drinking water, sanitation, and housing in the African countries and access to health facilities and paved roads in India are associated with upward mobility. Moving up the job ladder is linked to the probability of reducing poverty in all countries. Workers in Ghana and South Africa who are upwardly mobile are 11.8 and 6.9 percentage points more likely to move out of poverty compared with a worker who does not experience such mobility, while in India, the corresponding estimate is 2.2 percentage points. This finding suggests that policies supporting upward mobility, including public goods provision, development finance, and initiatives that promote the growth of firms offering high quality jobs, can contribute to poverty reduction.
Keywords: J62; I30; O12; 330; labour market mobility; jobs ladder; poverty; developing countries